2021
DOI: 10.3390/ijms22189881
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharide 2′-Fucosyllactose Induces Neuroprotection from Intracerebral Hemorrhage Stroke

Abstract: Intracerebral hemorrhage (ICH) occurs when brain blood vessels rupture, causing inflammation and cell death. 2-Fucosyllactose (2FL), a human milk oligosaccharide, has potent antiapoptotic and anti-inflammatory effects. The purpose of this study was to examine the protective effect of 2FL in cellular and rodent models of ICH. Hemin was added to a primary rat cortical neuronal and BV2 microglia coculture to simulate ICH in vitro. IBA1 and MAP2 immunoreactivities were used to determine inflammation and neuronal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Many studies included in this review supported the role of 2 -FL and fucosylated HMOS in learning and memory formation processes [53,[59][60][61][62]66,67]. This may be explained by the neuroprotective effects of 2 -FL in animal models [99,100], although the exact mechanism for this effect is unclear. LTP is often considered the cellular analog of learning and memory [101] and is widely used to assess synaptic transmission in neurons [102].…”
Section: Fucosylated Mos and Cognitionmentioning
confidence: 68%
“…Many studies included in this review supported the role of 2 -FL and fucosylated HMOS in learning and memory formation processes [53,[59][60][61][62]66,67]. This may be explained by the neuroprotective effects of 2 -FL in animal models [99,100], although the exact mechanism for this effect is unclear. LTP is often considered the cellular analog of learning and memory [101] and is widely used to assess synaptic transmission in neurons [102].…”
Section: Fucosylated Mos and Cognitionmentioning
confidence: 68%
“…Inflammation and ER stress are major causes of neurodegeneration after ischemic brain injury. We and others reported that suppression of inflammation or ER stress improved neural functions in stroke animals [ 11 , 16 ]. These data suggest that paeoniflorin and 5-hydroxymethylfurfural are the active ingredients in PM012, which may induce protection against ischemic brain injury through anti-inflammation and anti-ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Suppressing these processes prevents stroke-mediated degeneration. For example, we previously reported that 2-fucosyllactose reduced ischemia-mediated ER stress and inflammation in brain and improved locomotor behavior in stroke rats [ 11 ]. Interestingly, several active ingredients in PM012 also process anti-inflammatory or anti-ER stress properties [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from protecting against necrotising enterocolitis [6] or Streptococcus group B [7], HMOs may also provide other benefits to the neonate, including in neurodevelopment [8,9] and prevention of allergic diseases [10][11][12]. The development of a healthy gut microbiome, as a consequence of human milk oligosaccharides in the diet, has indications of longer-term benefit to the infant, including reduced incidence of inflammatory bowel diseases [13], neuroprotective effects [14] and small-molecule homeostasis [15]. In this context, understanding the principles of HMO synthesis as well as the conditions upon which HMOs are potentially digested by the infant gut [16], is a step towards answering the broad range of open questions.…”
Section: Introductionmentioning
confidence: 99%